Nanocellulose/Graphene oxide-modified PVDF membranes for efficient dye removal from wastewater: synthesis, characterization, and performance evaluation - Md. Rezaur, Rahman; Nur Fatmadewi, Dollah Chek; Muhammad Khusairy, Bakri; M. Shahabuddin, Ahmmad; Muneera S. M., Al-Saleem; Jehan Y., Al-Humaidi; Mohammed M., Rahman (Springer Nature, 2026)
Water pollution has remained a pressing global concern, particularly as access to clean water becomes increasingly limited. Wastewater treatment plays a crucial role in ensuring sufficient water can be supplied for daily needs. Membrane technology has become a promising method in ensuring the efficiency of eliminating contaminants from the wastewater, whereby poly(vinylidene fluoride) (PVDF) is commonly used in membrane fabrication. However, PVDF often faces limitations related to fouling, hydrophobicity, and mechanical stability, which can affect its long-term performance. To overcome these limitations, this research aims to develop, characterize, and analyze the performance of PVDF/GO/NC membranes for dye removal. The membranes were developed using the NIPS method, and characterization to determine the physical and chemical properties of the developed membranes was conducted using Fourier transform infrared (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), X-ray diffraction (XRD), membrane porosity measurement, and Ultraviolet-visible (UV-vis) spectroscopy. The membrane performance was evaluated through water permeation flux and dye removal efficiency using methylene blue (MB) as a model dye. The incorporation of nanocellulose (NC) and graphene oxide (GO) is expected to enhance the hydrophilicity, antifouling properties, and overall filtration performance of PVDF membranes, offering a more sustainable and effective approach to wastewater treatment.